Timber Business: Woodcutters and Merchants of Chiloe, 1850-1875 - Morales-Barrientos, D (UNIV MAGALLANES, 2014)
This paper refers to the exploitation of forest resources by the inhabitants of Chiloe Archipelago between 1850 and 1875. Likewise explains the trade flow of wood from Guaitecas and the east mountains upto its arrival at Ancud Port. On the other hand, highlights the role of the timber merchants in the archipelago and explains the mandatory debt strategy imposed to peasants.